Patient Recruitment into a Multicenter Randomized Clinical Trial for Kidney Disease: Report of the Focal Segmental Glomerulosclerosis Clinical Trial (FSGS CT). Issue 1 (30th October 2012) - Ferris, Maria; Norwood, Victoria; Radeva, Milena; Gassman, Jennifer J.; Al‐Uzri, Amira; Askenazi, David; Matoo, Tej; Pinsk, Maury; Sharma, Amita; Smoyer, William; Stults, Jenna; Vyas, Shefali; et al.
Abstract We describe the experience of the focal segmental glomerulosclerosis clinical trial (FSGS CT) in the identification and recruitment of participants into the study. This National Institutes of Health funded study, a multicenter, open‐label, randomized comparison of cyclosporine versus oral dexamethasone pulses plus mycophenolate mofetil, experienced difficulty and delays meeting enrollment goals. These problems occurred despite the support of patient advocacy groups and aggressive recruitment strategies. Multiple barriers were identified including: (1) inaccurate estimates of the number of potential incident FSGS patients at participating centers; (2) delays in securing one of the test agents; (3) prolonged time between IRB approval and execution of a subcontract (mean 7.5 ± 0.8 months); (4) prolonged time between IRB approval and enrollment of the first patient at participating sites (mean 19.6 ± 1.4 months); and (5) reorganization of clinical coordinating core infrastructure to align resources with enrollment. A Web‐based anonymous survey of site investigators revealed site‐related barriers to patient recruitment. The value of a variety of recruitment tools was of marginal utility in facilitating patient enrollment. We conclude that improvements in the logistics of study approval and regulatory start‐up and testing of promising novel agents are important factors in promoting enrollment into randomized clinical trials in nephrology. Clin Trans Sci 2013; Volume 6: 13–20